Russian roulette : the story of an assassin / 10. - Horowitz, Anthony, 1955- (Alex Rider adventure, 2013)
Presented with an unexpected assignment, Alex Rider's greatest nemesis, Yassen Gregoravich, recalls his life and the path that led him to become an assassin while his one-time friend, Alex's uncle, became a spy.